Potential hazard of the Neopuff T-piece resuscitator in the absence of flow limitation. Issue 6 (8th April 2009) - Hawkes, C P; Oni, O A; Dempsey, E M; Ryan, C A
Abstract : Objective: (1) To assess peak inspiratory pressure (PIP), positive end expiratory pressure (PEEP) and maximum pressure relief (Pmax ) at different rates of gas flow, when the Neopuff had been set to function at 5 l/min. (2) To assess maximum PIP and PEEP at a flow rate of 10 l/min with a simulated air leak of 50%. Design: 5 Neopuffs were set to a PIP of 20, PEEP of 5 and Pmax of 30 cm H2 O at a gas flow of 5 l/min. PIP, PEEP and Pmax were recorded at flow rates of 10, 15 l/min and maximum flow. Maximum achievable pressures at 10 l/min gas flow, with a 50% air leak, were measured. Results: At gas flow of 15 l/min, mean PEEP increased to 20 (95% CI 20 to 21), PIP to 28 (95% CI 28 to 29) and the Pmax to 40 cm H2 O (95% CI 38 to 42). At maximum flow (85 l/min) a PEEP of 71 (95% CI 51 to 91) and PIP of 92 cm H2 O (95% CI 69 to 115) were generated. At 10 l/min flow, with an air leak of 50%, the maximum PEEP and PIP were 21 (95% CI 19 to 23) and 69 cm H2 O (95% CI 66 to 71). Conclusions: The maximum pressure relief valve is overridden by increasing the rate of gas flow and potentially harmful PIP and PEEP can be generated. Even in the presence of a 50% gas leak, more than adequate pressures can be provided at 10 l/min gas flow. We recommend the limitation of gas flow to a rate of 10 l/min as an added safety mechanism for this device.